Association of Agriculture Occupational Exposure With Diabetes and Cardiovascular Risk Factors in South Indian Villages: REDSI Study - Velmurugan, Ganesan; Mohanraj, Sundaresan; Christy Yacob, Jenifer; Keppanan, Sundaravadivu; Rekha, Balakrishnan; Krishnasamy, Anbalagan; Shanmugarajan, Suresh; Boopathi, Seenivasan; Ayyapparaja, Anitha; Ayyapparaja, Prabhu Chandhran; RS, Tamilselvan; Gopalakrishnan, Manigandan; et al. (Frontiers in Cardiovascular Medicine, 2021)
There has been a huge increase in diabetes and its associated cardiovascular complications over the last decade, predominantly in the middle and low-income countries. In these countries, the majority live in rural areas. The REDSI (Rural Epidemiology of Diabetes in South India) study was aimed to analyze the prevalence of diabetes, cardiovascular risk factors and its complications in rural farming and non-farming villages in Tamil Nadu, South India. A research survey on prevalence of self-reported diabetes, cardiovascular risk factors (age, sex, obesity, hypertension, hypercholesterolemia, alcohol and tobacco use) and agricultural occupational exposure was executed among 106,111 people from 61 villages in the state of Tamil Nadu, South India during 2015-2018. Overall, we observed a diabetes prevalence of 11.9% in rural South India. A nearly two-fold higher prevalence of diabetes was observed among farming community (15.0%) compared to non-farming population (8.7%). Logistic regression analyses revealed a strong association with agrochemical exposure (P < 0.0001) and diabetes prevalence among rural farming people. Our survey indicates a high prevalence of diabetes in rural South India particularly among farming community. This survey in conjunction with other epidemiological and experimental studies raise the need for understanding the etiology of diabetes and other cardiovascular risk factors in rural communities.